Comparison of Yam Composite Cookies Sensory Characteristic Between Sugar and Stevia Sweeteners - Makiyah, Sri Nabawiyati Nurul; Setyawati, Ika; Rahmadhia, Safinta Nurindra; Tasminatun, Sri; Kita, Masaki (Journal of Agri-Food Science and Technology, 2024)
Yam (Dioscorea alata L.) is one source of carbohydrates with a low glycemic index. It is useful for controlling blood glucose levels. Yam has high carbohydrate and protein content but low sugar content. This research contributed to compare the sensory characteristics of the yam composite cookies between sugar and stevia sweeteners. This research is a quasi-experimental study with a cross-sectional design. Purple yam tubers were made into yam flour. The composite was made from yam flour and green bean flour (F1=100:0; F2= 80:20; F3= 60:40; F4= 40:60; F5= 20:80) (%w/w). Composites were processed into cookies with sugar and stevia sweeteners. Cookies with sugar and stevia sweeteners tested sensory characteristics to 31 in healthy adults aged 25-35. The results showed that the sensory characteristics of shape, size, color, texture, sweet taste and umami taste of yam cookies with sugar sweetener were not better than stevia sweetener. In contrast, the sub-variables of aroma, taste, and overall sweet potato cake with sugar were better than stevia. This implies that yam composite cookies with stevia sweeteners are healthier, but less desirable.